Biodiesel as a Plasticizer of a SBR-Based Tire Tread Formulation. (11th March 2013) - Cataldo, Franco; Ursini, Ornella; Angelini, Giancarlo
Abstract : The solubility parameter of a series of methyl esters of fatty acids, the components of biodiesel, was calculated using the group incremental method proposed by Van Krevelen. The solubility parameter of biodiesel was compared with that of a series of rubbers like EPDM, butyl rubber, polyisoprene, polybutadiene, SBR (with different content of styrene), and nitrile rubber (with different content of acrylonitrile) showing that biodiesel is an effective solvent of all the above mentioned rubbers with the exclusion of nitrile rubber. Indeed, it was experimentally verified that polyisoprene, polybutadiene and SBR are easily soluble in biodiesel while polystyrene gives a cloudy solution. Considerations on the solubility parameter of the biodiesel and of a series of rubbers have led to the conclusion that biodiesel behaves essentially as an internal lubricant in a diene rubber matrix, the same situation occurs with the common aromatic mineral oil plasticizer known as T-RAE. The experimental evaluation of biodiesel as plasticizer in an SBR-based rubber compound in comparison to an aromatic mineral oil have led to the primary conclusion that biodiesel is reactive with the sulphur curing agent subtracting sulphur to the crosslinking polymer chains and leading to a vulcanizatewith lower moduli, tensile and hardness and higher elongationsin comparison to a reference compound fully plasticized with an aromatic mineral oil. However, biodiesel seems a good low temperature plasticizer because the low elastic modulus observed is desired in a winter tire tread for a good grip on snow and ice. The present work is only an exploratory work, and the tire tread formulation with biodiesel was not optimized.